Pengaruh Model Problem Based Learning (PBL) terhadap Hasil Belajar Kognitif pada Mata Pelajaran IPAS Siswa Kelas VI SDN Bandungrejo 1 - Nafiatul Ulya; Ade Cyntia Pritasari (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the effect of the problem-based learning model on cognitive learning outcomes in the IPS subject of sixth-grade students at SDN Bandungrejo 1. This research uses a quantitative method with a pre-experimental design in the form of a one-group pre-test post-test. The data sampling technique used in this research is total sampling. The data collection technique involves using observation sheets to assess the implementation of learning activities by students and teachers, as well as pre-tests on cognitive learning outcomes. The results of this study show that the comparison of the total pretest score of 208 and the posttest score of 603, with an average pretest score of 8.66 and an average posttest score of 25.12. It can be concluded descriptively that the posttest scores after the treatment with the problem-based learning model were much higher compared to the pretest scores before the treatment was given. The results of the non-parametric statistical test calculation using the Wilcoxon signed rank test show an Asymp Sig. (2-tailed) value of < 0.001 < 0.05, which means Ho is rejected and Ha is accepted. It can be concluded that there is a difference in pretest and posttest results after the treatment using the problem-based learning model, which means that the use of the problem-based learning model affects the cognitive learning outcomes of sixth-grade students at SDN Bandungrejo 1.